Experiências dos trabalhadores das Lojas Pernambucanas no contexto da reestruturação produtiva (1970-2000) - Maschio, Maralice (2008)
This dissertation proposes reflect on the process of restructuring in Pernambucanas as productive history of the workers themselves. The need has been to show that a process can be seen, in the Pernambucanas case, just as evaluation and experience of the entrepreneur, but as a field of disputes between those involved, which includes customers and specially the workers. Sources such as newsletters, magazines, works of memorialist, produced by the company or on the orders it, allowed indicate the strategies of the company to try to promote the so-called consent in the sphere of production. But talking with the oral narratives of officials and former officials of the Pernambucanas who lived and live the process, it is perceived as the ways they mean and shape changes in their ways of living and working, dictating dynamic in this space. I tried to analyze the store in an area of productive game in which the worker dispute with the boss felt about their work at the same time that the exploitation consent on their work, using artifice or gaps left by the system itself, to take advantage of situations, uses them to their own benefit